Prototipe Alat Pengekstrak Pati Sagu Tipe Mixer Rotary Blade Bertenaga Motor Bakar - Darma Darma; Istalaksana Istalaksana; Andreas Andreas (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2010)
Papua and West Papua Province have a large potential of sago. Approximately 994,000 hectares, mostly natural sago forest was existed in this area. Sago starch has long been an important source of nutrition troughout Papua. Product of sago palm is not only starch as source of carbohydrate for food stuff, but also for basic material of industries such as paper, plywood, hardboard, and food indutries. Traditional methods are used for starch extraction in almost all part of Papu, which is not efficient and production capacity is very low. The effort to increase sago starch production could be carry out by introducing mechanical equipment (traditional to mechanized processing). The objective of this research was to design mixer rotary blade of sago starch extraction powered by internal combustion engine. The result was prototype of mechanical sago starch extractor. The prototype has high performance with extraction capacity 160 kg of disintegrated pith per hour or equal to 33 kg of wet starch per hour, extractable starch more than 99 % while starch losses in hampas less lhan 1 %. Hopefully, application of this machine to the sago farmer will transform agricultural system from subsistence to commercial. It means that increasing of economic income. In conclusion, technically and economically this prototype was feasible.ABSTRAKProvinsi Papua dan Papua Barat memiliki potensi sagu yang sangat besar. Sekitar 994.000 hektar yang sebagian besar merupakan hutan sagu alam terdapat di kedua provinsi ini. Pati sagu telah lama digunakan sebagai sumber nutrisi bagi penduduk asli papua. Pati sagu tidak hanya digunakan sebagai sumber karbohidrat, namun juga digunakan seba- gai bahan dasar industri kertas, plywood, hardbord, dan pangan. Pengolahan sagu secara tradisional yang dilakukan oleh masyarakat tidak efisien dan kapasitas produksinya sangat rendah. Peningkatan produksi dapat dilakukan dengan mengintroduksi peralatan pengolahan mekanis untuk merubah metode pengolahan tradisional ke pengolahan meka- nis. Tujuan penelitian ini adalah merancang alat ekstraksi pati sagu tipe mixer rotary blade bertenaga motor bakar. Hasilnya adalah prototipe alat ekstraksi pati dengan performansi bagus. Kapasitas ekstraksi adalah 160 kg hancuran empulur per jam, atau setara dengan 33 kg pati segar per jam, jumlah pati yang dapat diekstrak lebih dari 99 % sedan- gkan kehilangan pati yang terikut ke ampas kurang dari 1%. Aplikasi alat ini ke masyarakat petani sagu diharapkan akan merubah sistim pertanian yang bersifat subsistence ke sistim komersial. Sebagai kesimpulan, alat ekstraksi pati sagu yang telah dihasilkan layak secara teknis maupun ekonomis.